Reproduction of Distinct Varroa destructor Genotypes on Honey Bee Worker Brood - Li, Wenfeng (Insects, 2019)
Honey bees play important roles in pollination for many crops and wild plants, but have been facing great threats posed by various pathogens and parasites. Among them, Varroa destructor, an obligate ectoparasite of honey bees, is considered the most damaging. Within the last century, V. destructor shifted from the original host, the Asian honey bee Apis cerana to the new host, the European honey bee A. mellifera. However, the reproduction of Varroa mites, especially of different haplotypes in the two hosts, is still largely unknown. In this study, we first investigated the existing Varroa haplotypes in local colonies in southern China, and then compared the reproduction of different haplotypes on the worker brood of both the original and new hosts by artificial inoculation. We confirmed that there are two haplotypes of V. destructor in southern China, one is the Korea haplotype and the other is the China haplotype, and the two types parasitized different honey bee species. Although Varroa females from A. mellifera (Korea haplotype) are able to reproduce on the worker brood of both honey bee species, they showed better reproductive performance in the new host A. mellifera with significantly higher fecundity (number of offspring per mother mite) and reproductive rate (number of adult daughters per mother mite), suggesting that this parasite gains higher fitness after host shift. The data further showed that a short stay of Varroa females inside the A. cerana worker cells decreased their fecundity and especially the reproductive rate in a time-dependent manner, suggesting that the A. cerana worker cells may inhibit Varroa reproduction. In contrast, Varroa mites derived from A. cerana colonies (China haplotype) were entirely sterile in A. mellifera worker cells during two sequential inoculations, while the control mites from A. mellifera colonies (Korea haplotype) reproduced normally. In addition, all the infertile mites were found to defecate on the abdomen of bee pupae. We have revealed that two haplotypes of V. destructor exhibit differential reproduction on the worker brood of the original and new host honey bees, providing novel insights into the diversity and complexity of the reproduction of V. destructor.